Analisis Penetapan Nilai Jual Obyek Pajak Bumi dan Bangunan Sektor Perkebunan sebagai Upaya Peningkatan Sumber Pendapatan Daerah - Kadir, Abdul (Journal of Education, Humaniora and Social Sciences (JEHSS), 2018)
The purpose of this paper is to explore the sources of income from the plantation sector, through policies in the form of changes in determining the amount of Tax Object Sales Value, Land and Building Tax (PBB NJOP) based on macroeconomic variables and crop productivity as well as the effect on Regional Original Income (PAD ) This paper focuses on NJOP by using primary data to analyze stakeholder perceptions and secondary data for path equation analysis. The results showed that simultaneously the variables of economic growth and population density had a significant effect on NJOP at a 95% confidence level. Partially economic growth variables and population density have a significant effect on NJOP at a 95% confidence level. The ability of economic growth variables and population density together can provide an explanation of the NJOP variation of 38.70%. Together, the variables of economic growth, population density and NJOP have a significant effect on the United Nations at a 95% confidence level. Partially economic growth, population density and NJOP have a significant effect on the United Nations at a 95% confidence level. The ability of economic growth, population density and NJOP are jointly able to provide an explanation of the UN variation of 67.20%. Simultaneously the variables of economic growth, population density, NJOP and PBB significantly affected PAD at 95% confidence level. Partially, the variables of economic growth, population density, NJOP and PBB significantly affected PAD at 95% confidence level. Variables of economic growth, population density, NJOP and PBB together are able to provide an explanation of PAD variation of 67.70%.